P873 The psycho-emotional experience of pregnancy in women with IBD and correlation with gut microbiome. (16th January 2018) - Eisele, C; Carreon, I; Huang, R; Hu, J; Nair, N; Porat Jankelson, R; Torres, J; Colombel, J -F; Peter, I; Keefer, L
Abstract: Background: IBD patients experience greater stress, anxiety and depression which impair quality of life and increase disease burden. It is not known whether women with IBD have more stress and anxiety than healthy controls (ctl) during pregnancy or how these psychosocial factors influence their experience of pregnancy. Methods: We investigated measures of stress, anxiety and depression affecting pregnant women with and without IBD participating in the MECONIUM (Exploring MEChanisms Of IBD traNsmission In Utero through the Microbiome) Study. 34 IBD women (median age = 33, 62%CD, 88%white, median parity = 2) and 145 matched ctls, all pregnant/recent delivery, completed the Perceived Stress Scale-14, Autonomic Function Questionnaire (AFQ), Brief Symptom Inventory (BSI) and the Pregnancy Experiences Scale (PES). Questions were answered based on current feelings. Women not currently pregnant answered the PES based on their most recent pregnancy. Mean scores comparison was conducted between four groups (IBD vs. ctl pregnant, IBD vs. ctl not pregnant) using one-way ANOVA with planned comparisons. We conducted a stepwise linear regression to find potential predictors of negative pregnancy experiences in IBD. We ran correlation network analysis between stress variables and pregnancy stool microbiome profiled using 16s rRNA sequencing. Results: There were significant differences in the mean scores of the four groups of subjects across four subscales: PES frequency, intensity and total uplifts (positive feelings about pregnancy) and the BSI somatic symptoms subscale, with higher mean uplift scores in the ctl/non-pregnant groups vs. pregnant/IBD groups and higher BSI somatic scores in the pregnant groups vs. non-pregnant groups. Higher BSI somatic scale scores and parity were significant predictors of hassles (negative feelings about pregnancy) in pregnant women with IBD. There was strong crosstalk between psychological scores and maternal gut microbial genera at third trimester but not second trimester. Conclusions: A negative pregnancy experience for IBD women is predicted by somatic symptoms of psychological distress as indicated by the BSI and parity. Higher crosstalk between microbiota and psychological scores was observed in stool collected during third trimester than second trimester. Further analysis of microbiome correlation to psychological variables is on-going.